Ambivalent Sexism in the State of Qatar: Gender Roles and Patriarchal Attitudes - Lari, Noora (Hawwa, 2024)
This article examines public attitudes toward ambivalent sexism in the State of Qatar, which has taken considerable initiatives to prioritize women’s empowerment strategies and promote equality between men and women. It investigates whether these equality initiatives are reflected in nationals’ attitudes toward women by measuring scores on the Ambivalent Sexism Inventory (ASI). While prior research has focused almost exclusively on the role of social implications, much less has been explored regarding the public sentiments underlying traditional gender roles and patriarchal attitudes in Qatari society. This study uses original survey data from a national sample of a 2019 survey. The results of the novel analytical descriptive approach used here suggest that individuals in Qatar are highly sexist on average, indicating that as a nation, Qatar scores low on gender equality measures. The analysis also reveals that benevolent sexism is evaluated more positively than hostile sexism, although its underlying dimensions correlate with patriarchal views and gender stereotyping in the context of high gender inequality. These findings are especially important considering the ever-emerging dynamics of gender roles and the increased efforts being gradually expended for improved gender parity.